Estimation of stature and body weight in Slovak adults using static footprints: A preliminary study. (September 2018) - Caplova, Zuzana; Švábová, Petra; Fuchsová, Mária; Masnicová, Soňa; Neščáková, Eva; Bodoriková, Silvia; Dörnhöferová, Michaela; Beňuš, Radoslav
Highlights: Body weight and stature prediction equations from footprints were developed. No intersexual and bilateral differences were found. The lateral diameters of footprint show the highest accuracy. The non-contact fifth toe was observed in maximum 7% of footprints. The trend of under- and overestimation was identified. Abstract: The stature and the body weight as part of the biological profile can aid the personal identification. The dimensions of the human foot, as well as the footprint, can be used for the prediction due to the existence of its positive correlation with the stature and body weight. Five diagonal axes and ball breadth of bilateral static footprints of 132 young Slovak adults were obtained. All diameters were larger in a male group than female group. No bilateral differences were found except the first diagonal axis and ball breadth. A positive correlations between the selected footprint diameters with the stature (r = 0.37–0.64) and the body weight (r = 0.29–0.71) were confirmed. The linear and multiple regression prediction equations were developed. A stature prediction equation using the most lateral diameters (the fourth and fifth diagonal axis) exhibited the highest accuracy ranging from 4 to 7.5 cm. Similar results were found for the body weight estimation of the male and mixed group. In the female group, the most medial axis (first and second) exhibited the highest accuracy. The body weight estimation accuracy ranges from 9.09 to 11.09 kg. The real and predicted stature and body weight were compared and found differences were lower than calculated SEEs. Thresholds and prediction trend of under- or overestimation was identified. The results of the present study show that selected measurements of static footprints could be used to predict stature and body weight but should be applied only for Slovaks due to population specificity.